1983
DOI: 10.1002/dev.420160106
|View full text |Cite
|
Sign up to set email alerts
|

The separate and combined effects of early undernutrition and environmental complexity at different ages on cerebral measures in rats

Abstract: Rats were either undernourished or fed normally during the suckling period, then at 1 and 5 months of age littermates were housed in enriched or impoverished environments for 30 days. The undernutrition caused lasting reductions in the weight and size of the cerebrum and in parameters of the hippocampus, but significant deficits were not observed in the thickness and area of the occipital cortex. Differential housing differed from early undernutrition in that its largest effects were on cortical parameters, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Enriched housing has also been shown to alter gross measures of brain morphology in noradrenaline-depleted rats 63 , in malnourished rats (e.g. 9,46,47,48) and vasopressin deficient rats of the mutant Brattleboro strain34, 35. However, other researchers using adult hemidecorticate rats 86 , prenatally X-irradiated microcephalic rats SO , noradrenaline-depleted rats 8 , 65, or malnourished rats 15 have failed to observe any influence of differential housing on gross neuroanatomy, although most of them found housing effects on behavior in brain-damaged animals or on neuroanatomical measures in intact control animals. The gross measures considered were possibly too gross to reveal subtle changes accompanying functional modifications.…”
Section: Environmentally-induced Brain Modificationsmentioning
confidence: 99%
“…Enriched housing has also been shown to alter gross measures of brain morphology in noradrenaline-depleted rats 63 , in malnourished rats (e.g. 9,46,47,48) and vasopressin deficient rats of the mutant Brattleboro strain34, 35. However, other researchers using adult hemidecorticate rats 86 , prenatally X-irradiated microcephalic rats SO , noradrenaline-depleted rats 8 , 65, or malnourished rats 15 have failed to observe any influence of differential housing on gross neuroanatomy, although most of them found housing effects on behavior in brain-damaged animals or on neuroanatomical measures in intact control animals. The gross measures considered were possibly too gross to reveal subtle changes accompanying functional modifications.…”
Section: Environmentally-induced Brain Modificationsmentioning
confidence: 99%
“…In fact, it has been reported that environmental stimulation produces changes in structural, neurochemical and functional parameters in the central nervous system of the rat (26)(27)(28)(29). It has been suggested that these effects of early protein malnutrition may be partially reversed by environmental stimulation offered during malnutrition, or later during the nutritional recovery period (26,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the labeling index and cell cycle time, they concluded that undernutrition markedly diminished the rate of dentate granule cell acquisition. Katz and Davies (1983) measured the width of the hippocampus in rats fed one-half their usual diet during the period of gestation and lactation, during lactation alone, or during lactation and the post-weaning period. They observed a significant decrease in width only in rats in which undernutrition included the period of gestation.…”
Section: Introductionmentioning
confidence: 60%